1988
DOI: 10.1159/000199729
|View full text |Cite
|
Sign up to set email alerts
|

Adrenergic Effects on Secretion of Amylase from the Rat Salivary Glands

Abstract: The present study was undertaken to investigate the effect of adrenergic agents on secretion of amylase from the salivary glands in vivo. Saliva was collected from the distal oesophagus in conscious rats. Adrenaline increased the concentration of amylase in saliva and serum significantly. The result of infusion of alpha- and beta-adrenergic antagonists as well as noradrenaline and isoproterenol showed that secretion of salivary amylase is predominantly mediated by stimulation of beta-adrenergic receptors, espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
1
11
1
Order By: Relevance
“…Compared to control rats receiving saline-infusion only, NEbut also EPI-infusion elicited significantly higher sAA levels (Skov Olsen et al, 1988). With respect to observed associations between stress-induced NE and sAA release, results of that animal study may be interpreted in that stress-induced NE increases mediate (at least in part) sAA release (Skov Olsen et al, 1988). While in humans, a direct effect of NEor EPI-infusion on sAA has not yet been investigated, studies using the non-selective beta-adrenergic agonist isoprenaline similarly observed a rise in sAA levels following isoprenaline infusion (Katz and Mandel, 1968;Speirs et al, 1974).…”
Section: Introductionmentioning
confidence: 68%
See 4 more Smart Citations
“…Compared to control rats receiving saline-infusion only, NEbut also EPI-infusion elicited significantly higher sAA levels (Skov Olsen et al, 1988). With respect to observed associations between stress-induced NE and sAA release, results of that animal study may be interpreted in that stress-induced NE increases mediate (at least in part) sAA release (Skov Olsen et al, 1988). While in humans, a direct effect of NEor EPI-infusion on sAA has not yet been investigated, studies using the non-selective beta-adrenergic agonist isoprenaline similarly observed a rise in sAA levels following isoprenaline infusion (Katz and Mandel, 1968;Speirs et al, 1974).…”
Section: Introductionmentioning
confidence: 68%
“…To date, the role of alpha-adrenergic receptors in mediation of stress-induced sAA increases is still unclear. In the previously mentioned pioneer infusion study in rats blockade of alpha1-and alpha2-adrenergic receptors by phenoxybenzamine reduced EPI-infusion-induced sAA increases (Skov Olsen et al, 1988). Notably, in that study blockade of alpha-adrenergic receptors was associated with lower inhibition of EPI-infusion induced sAA release as compared to non-selective beta-adrenergic blockade by propranolol (Skov Olsen et al, 1988).…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations